The Role of Mediators In Divorce Mediation Efforts at The Religious Court of Jambi City From an Islamic Law Perspective - Maryani Maryani; Ruslan Abdul Gani; Zulqarnain Zulqarnain; Kurniadi Darmawan Saputra (Journal of Social Research, 2025)
This study aims to find out the mediation process, the role of mediators, and the obstacles to the mediation process in divorce cases at the Jambi City Religious Court. The research method used is qualitative research with a descriptive analytical approach. The type of research used in this study is field research, which is data collected or collected to obtain information and valid data to answer problems in this study obtained from the results of field studies which are then combined with data obtained from literature studies, so that accurate data is obtained. Data was obtained through direct observation, interviews with mediators in order to find out the role of mediators in efforts to mediate divorce cases at the Jambi City Religious Court, as well as analysis of related documents. The results of the study show that the mediation process at the Jambi City Religious Court occurs in 5 stages, namely: The first stage, the existence of a case The fourth stage is to make an agreement by holding a joint meeting. The fifth stage is the implementation of the agreement by implementing the content of the agreement with the parties. If the mediation is successful, the mediator makes a peaceful decision (in divorce cases, the panel makes a decision to revoke it). Furthermore, if mediation fails, the panel can continue to examine the case and make a litigation decision.